Effects of Role Models on Undergraduate Students ’ Academic Performance, Sense of Belongingness, Self-efficacy and Persistence in Science, Technology, Engineering and Mathematics (STEM) - Kinyota, Mjege Kinyota (Papers in Education and Development, 2023)
This study investigated the extent to which selected aspects of role modelling predict undergraduate students ' performance, self-efficacy, persistence and sense of belongingness to Science, Technology, Engineering and Mathematics (STEM). The study involved a total of 749 final-year STEM students from three public universities in Tanzania. Overall, results from hierarchical regression analysis indicated no significant effects. However, few exceptions were noted. For instance, the proportion of female instructors significantly predicted academic performance for female students. Further, personal variables such as gender identification, majoring in engineering and attending a private school had significant influence on some dependent variables, with notable variations across gender. The implications of this study on policy and future research are discussed. Keywords: gender, higher education, role models, STEM, Tanzania